Transforming Physics Learning: Developing AI-Based Interactive Videos to Understand Newton's Laws - Hanisa Feranti Hanisa; Sardianto Markos Siahaan (Physics Education Research Journal, 2025)
This study aims to describe the results of the needs analysis conducted at SMA Negeri 3 Prabumulih as a basis for developing artificial intelligence-based learning videos for differentiated physics learning. Data analysis was carried out using validation sheet data, questionnaires and interviews. This study serves as a preliminary study at the definition stage, where researchers ensure that the products developed meet the needs of teachers and students. The results of the questionnaire as many as 92.3% (150 respondents), stated that they agreed that SMA uses learning videos for every physics material. This is because physics material is learning material that is difficult for students to understand. The results of the description of the assessment data by the media validator on the media in the form of learning videos are in the very good qualification, this is categorized as very good. The trial results show that products that are equipped with practical aspects shown to teachers and students are categorized as very practical. So the level of validity of this learning video media is said to be very valid because it is in the range of 92.82% and the level of practicality of the media in the form of learning videos is 97.28% categorized as very good.